The Impact of Incomplete Nutrient Consumption in the Southern Ocean on Global Mean Ocean Nitrate δ15N. Issue 2 (21st February 2023) - Fripiat, F.; Sigman, D. M.; Martínez‐García, A.; Marconi, D.; Ai, X. E.; Auderset, A.; Fawcett, S. E.; Moretti, S.; Studer, A. S.; Haug, G. H.
Abstract: It is understood that the global mean ocean nitrate δ 15 N is set by the δ 15 N of the input of fixed nitrogen (N) to the ocean (mostly N2 fixation) and the net isotopic discrimination of fixed N loss (mostly denitrification). Here, we demonstrate that, in addition to the fixed nitrogen input/output budget, the isotopic discrimination of nitrate assimilation in the Southern Ocean also plays a role in setting the δ 15 N of both deep ocean nitrate and global mean ocean nitrate. A prognostic model is used to simulate the global overturning circulation, focusing on the Southern Ocean overturning cell that ventilates the global pycnocline. N2 fixation and denitrification occur mainly in the model's surface and pycnocline boxes, as is appropriate given the observations. Experiments with this model indicate that, at a steady state, pycnocline nitrate δ 15 N is mostly controlled by the ocean's fixed N budget. Simultaneously, partial nitrate assimilation in the Southern Ocean sets the nitrate δ 15 N difference between the pycnocline and the deep ocean, lowering the δ 15 N of deep ocean nitrate and thus also of global mean ocean nitrate. The Southern Ocean's impact on deep and mean ocean nitrate δ 15 N depends on (a) the degree of nitrate consumption in the Southern Ocean surface waters and (b) the proportion of water that enters the pycnocline by subduction from the Southern Ocean surface. Including the effect of the Southern Ocean on mean ocean nitrate δ 15 N modestly reduces a previously calculated imbalance between fixed N inputs and outputs. Moreover, this effect has implications for paleoceanographic N isotope records. Key Points: At steady state, the ocean's fixed nitrogen input/output budget sets global pycnocline nitrate δ 15 N Partial nitrate assimilation in the Southern Ocean sets the nitrate δ 15 N difference between the pycnocline and the deep ocean Relative to the fixed nitrogen budget, partial nitrate assimilation in the Southern Ocean lowers the δ 15 N of deep and mean ocean nitrate